2016
DOI: 10.1111/irv.12416
|View full text |Cite
|
Sign up to set email alerts
|

Influenza‐like illness‐related emergency department visits: Christmas and New Year holiday peaks and relationships with laboratory‐confirmed respiratory virus detections, Edmonton, Alberta, 2004–2014

Abstract: BackgroundEmergency department (ED) visit volumes can be especially high during the Christmas–New Year holidays, a period occurring during the influenza season in Canada.MethodsUsing daily data, we examined the relationship between ED visits for the chief complaint “cough” (for Edmonton, Alberta residents) and laboratory detections for influenza A and respiratory syncytial virus (RSV) (for Edmonton and surrounding areas), lagged 0–5 days ahead, for non‐pandemic years (2004–2008 and 2010–2014) using multivariab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Lower respiratory tract infections (LRTIs) accounted for greater than 90% of all DALYs, with approximately 35% of cases occurring in children less than 5 years old (13,14). The impact of respiratory infections on human health is reflected in the large number of hospital and emergency room visits for both adults and children (e.g., in the United States, there are 140,000 to 710,000 FLU-related hospital-izations per year), where respiratory viral infection is the most common reason to seek medical care (15,16).…”
Section: Epidemiology and Clinical Presentation Of Acute Respiratory mentioning
confidence: 99%
See 1 more Smart Citation
“…Lower respiratory tract infections (LRTIs) accounted for greater than 90% of all DALYs, with approximately 35% of cases occurring in children less than 5 years old (13,14). The impact of respiratory infections on human health is reflected in the large number of hospital and emergency room visits for both adults and children (e.g., in the United States, there are 140,000 to 710,000 FLU-related hospital-izations per year), where respiratory viral infection is the most common reason to seek medical care (15,16).…”
Section: Epidemiology and Clinical Presentation Of Acute Respiratory mentioning
confidence: 99%
“…Antibacterial prescription rates did not vary between groups; however, there was a statistically significant difference between antiviral prescription rates: the FLU-positive group was more likely to be treated with an antiviral agent (80/105 [81%] treated) than were patients in the non-influenza virus pathogen group (6/109 [5.5%]) and the no-pathogen-detected group (2/81 [2.5%]) (P Ͻ 0.001) (254). Respiratory panel use allows for more comprehensive characterization of viruses for general epidemiology/surveillance (15,265) and outbreak investigation. Other, less tangible but important, benefits to respiratory viral panel use may also include improved patient and physician satisfaction with an improved test turnaround time.…”
Section: Molecular Panel Testing For Respiratory Viruses (I) Defininmentioning
confidence: 99%
“…All reviewed works primarily evaluated transmission patterns of influenza during extreme mass gatherings [20,21,34]. Otherwise, researchers rarely considered differential effects of holidays at different times of the year, instead combining all holiday weeks under one dichotomous variable [13] or isolating their analyses to a single time of the year [35]. While some works have reviewed differences in incidence risk ratios (IRRs) before, during and after individual school holidays, none have explored holiday categorisation effects on these IRRs or seasonal signatures [2,3,6].…”
Section: Discussionmentioning
confidence: 99%
“…[1] The number of emergency department visits for influenza-like illnesses is estimated at around 100 per 100 000 inhabitants. [2] The management of these epidemics is therefore a real medical challenge. Many studies have shown increased emergency department stay lengths, bed use and premature patient departures during influenza epidemics.…”
Section: Introductionmentioning
confidence: 99%